2019
DOI: 10.1109/tvcg.2019.2934614
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Learning for Identifying Relevant Tweets to Support Real-time Situational Awareness

Abstract: InterfaceAutomated Label Verify Label Fig. 1. Our interactive learning framework allows users to train text relevance classifiers in real-time to improve situational awareness.In this example, a real-time tweet regarding a car accident is incorrectly classified as "Irrelevant". Through the SMART 2.0 interface, the user can view its label and correct it to "Relevant", thereby retraining and improving the classifier for incoming streaming data.Abstract-Various domain users are increasingly leveraging real-time s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…The Social Media Analytics and Reporting Toolkit (SMART) [17,18] is a system for visual analysis of geotagged, publiclyavailable real-time tweets to enhance situational awareness and expedite emergency response. SMART has been used by over 300 first responders in 70 organizations for major events, such as presidential inaugurations and sports games.…”
Section: Integration With Smartmentioning
confidence: 99%
See 2 more Smart Citations
“…The Social Media Analytics and Reporting Toolkit (SMART) [17,18] is a system for visual analysis of geotagged, publiclyavailable real-time tweets to enhance situational awareness and expedite emergency response. SMART has been used by over 300 first responders in 70 organizations for major events, such as presidential inaugurations and sports games.…”
Section: Integration With Smartmentioning
confidence: 99%
“…In addition, SMART users have frequently indicated that they would prefer more data to less, even if it is inaccurate, since they might be able to identify relevant tweets that would otherwise not be present without geolocation inference. SMART's integrated interactive learning allows users to train its relevance filters in real-time using a human-in-the-loop learning solution to filter out noise [17].…”
Section: Integration With Smartmentioning
confidence: 99%
See 1 more Smart Citation
“…SMART [6,9] was developed at Purdue University through an iterative, user-centered design by collecting feedback from the first responder community to ensure its usefulness. SMART provides a user-friendly, graphical web-based user interface, hiding the complexity of advanced algorithms filtering and summarizing social media data, which allows users to interactively explore, filter, and visualize trends and anomalies in real-time geo-tagged Twitter data.…”
Section: Overview Of Smartmentioning
confidence: 99%
“…There has been considerable research on the potential and use of social media data for situational awareness, such as disaster response, event monitoring, or public sentiment analysis [1][2][3][4][5]. In particular, researchers have provided visual analytics approaches combining visualization and data analysis [2][3][4][5][6][7], geoparsing for crisis-mapping [7,8], cloud-based mobile services for on-the-ground information [14], and data mining and natural language processing techniques such as clustering and named entity recognition [15].…”
Section: Introductionmentioning
confidence: 99%